Impact of stopping the use of iron fortified iodised salt on Hb levels - Prabhakar, Kamini; Kumari, Honey; Kalaivani, K.; Ramachandran, Prema (International Journal Of Community Medicine And Public Health, 2023)
Background: Research studies have shown that use of iron fortified iodised salt (DFS) improved Hb in women, children and men. There are no publications on impact of stopping DFS on Hb levels. Methods: A community-based randomised study to assess the impact of DFS use on Hb was being carried out in Delhi. Between April-September 2020 salt could not be supplied and families were requested to purchase iodised salt (IS) from the market and use it. Blood samples from persons from these families were collected to assess impact of not using DFS for 6 months on Hb. Results: Comparison of mean Hb after 12 months use of the allocated salt and Hb after six-month use of IS by all three groups showed that: (1) there was a small reduction in Hb in all three groups after using IS for 6 months; fall was statistically significant in women in group 3; (2) women who had earlier used DFS had higher mean Hb and ferritin as compared to those who had used IS, both after 12 months of use of DFS and after 6 months of use of IS; (3) changes in ferritin varied and were not consistent. Conclusions: DFS users continued to have a higher mean Hb as compared to IS users even after discontinuing use of DFS for 6 months. The impact of this higher Hb when they restart using DFS for further 12 months has to be investigated.